2004
DOI: 10.1007/s11325-004-0147-7
|View full text |Cite
|
Sign up to set email alerts
|

C-Fiber Activation Exacerbates Sleep-Disordered Breathing in Rats

Abstract: We reported previously that activation of vagal feedback by protoveratrines or serotonin exacerbates sleep apnea in rats, but each of these agents activates multiple afferent fiber types. To elucidate the specific impact of C-fiber activity on sleep apnea, the present study utilized capsaicin (CAP), which stimulates C-fibers via the CAP receptor. Nine adult Sprague-Dawley rats were instrumented for chronic polysomnography and recorded for 6 hours on four occasions. Prior to each recording, the animals received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…We showed that laboratory rats express spontaneous central sleep apneas, and apnea frequency varies among rat strains. [11][12][13][14][15] We also demonstrated that hyperoxia increased the frequency of spontaneous apneas in outbred Sprague-Dawley rats. 14 It is unknown how SRBD may vary across the circadian day.…”
supporting
confidence: 54%
“…We showed that laboratory rats express spontaneous central sleep apneas, and apnea frequency varies among rat strains. [11][12][13][14][15] We also demonstrated that hyperoxia increased the frequency of spontaneous apneas in outbred Sprague-Dawley rats. 14 It is unknown how SRBD may vary across the circadian day.…”
supporting
confidence: 54%
“…In addition, pharmacologic hypertension evoked, for example, by infusion of phenylephrine, can prolong expiratory time, but does not commonly evoke apnea. Further, activation of pulmonary vagal stretch receptors provokes apnea via the Hering-Breuer reflex (Younes et al, 1974; Carley et al, 2004) without activation of baroreceptors and 5-HT can elicit dose-dependent apnea via activation of vagal afferents (Yoshioka et al, 1992, 1996; Radulovacki et al, 2007). Together, these facts suggest that the 5-HT evoked apneic response reflects activation of non-baroreceptor vagal afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Carley and coworkers further demonstrated that two other pharmacologic activators of vagal afferents, capsaicin (Hedner et al 1985) and protoveratrine (Clozel et al 1990) also increased spontaneous SRBD in rats (Trbovic et al 1997; Carley et al 2004). Interestingly, unlike serotonin, capsaicin, which activates primarily c-fibers, and protoveratrine, which stimulates free nerve endings, increased apnea expression only during NREM sleep (Figs.…”
Section: Vagus Nerve Apneic Reflexesmentioning
confidence: 99%